2022
DOI: 10.18231/j.ijca.2022.035
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of nalbuphine and fentanyl as adjuvants to bupivacaine in unilateral spinal anaesthesia in patients undergoing lower limb orthopaedic surgeries

Abstract: Unilateral spinal anaesthesia is a technique used to avoid hemodynamic changes and early recovery. Adjuvants are added to prolong post operative analgesia, this study was done to compare nalbuphine (0.8mg) and fentanyl (20µg) as adjuvants to 0.5% bupivacaine Heavy in unilateral spinal anaesthesia for patients undergoing lower limb orthopaedic surgeries. Randomized double blind study in patients posted for lower limb orthopaedic surgery in a teritiary care center.Unilateral spinal anaesthesia was given to 68 el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
0
0
Order By: Relevance
“…Similar results were obtained by Garg et al [ 12 ] and Gupta et al [ 13 ] who inferred that the mean time for the first rescue analgesic request in the nalbuphine group was significantly better when compared to the fentanyl group. However, there were a few divergences from our observations from Srinivasaiah et al [ 14 ] and Gomaa et al [ 15 ] who found no significant difference in the duration of analgesia between nalbuphine and fentanyl. The main presumption for such a divergence in findings could be attributed to a lesser dose of nalbuphine employed in both trials in contrast to us.…”
Section: Discussioncontrasting
confidence: 99%
“…Similar results were obtained by Garg et al [ 12 ] and Gupta et al [ 13 ] who inferred that the mean time for the first rescue analgesic request in the nalbuphine group was significantly better when compared to the fentanyl group. However, there were a few divergences from our observations from Srinivasaiah et al [ 14 ] and Gomaa et al [ 15 ] who found no significant difference in the duration of analgesia between nalbuphine and fentanyl. The main presumption for such a divergence in findings could be attributed to a lesser dose of nalbuphine employed in both trials in contrast to us.…”
Section: Discussioncontrasting
confidence: 99%